PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK SMP KELAS VIII DALAM PENERAPAN MODEL PEMBELAJARAN MEANS-ENDS ANALYSIS - siti imaniah; nurjanah nurjanah (UJMES (Uninus Journal of Mathematics Education and Science), 2018)
The low ability of students in mathematical problem solving especially to face story question that relating with daily life becomes problem statement in this research. The purpose of this research is to know that increased mathematical problem solving ability of students using Means Ends Analysis (MEA) model is better or not than using problem based learning model (PBL). The approach of this research is qualitative and quantitative by using quasi experimental method. The population in this research is eight grade students of one of junior high school in Bandung. The data were collected by test of mathematical problem solving ability as main instrument and teacher’s sheet observation as supporting instrument. The conclusion of this research is increased mathematical problem solving ability of students using MEA model is better than using PBL model .